Between Na Young and Nora: Self-Concept, Diasporic Identity, and Psychological Congruence in Past Lives (2023) - Evelyn Agastya Intany; Much. Koiri (English Department, Universitas Negeri Surabaya, 2026)
This study examines how Nora Moon’s self-concept and diasporic identity are cinematically constructed in Past Lives (2023) through Carl Rogers’ humanistic psychology. Although previous studies have discussed identity and diaspora in film, limited attention has been given to how cinematic language represents psychological incongruence, self-reflection, and movement toward congruence. Using a qualitative textual and visual analysis, this study analyzes selected dialogues, character interactions, mise en scène, framing, silence, facial expressions, and spatial composition in key scenes involving Nora, Hae Sung, and Arthur. The findings show that Nora’s self-concept develops through the tension between her real self, represented by her Korean childhood identity as Na Young, and her ideal self, shaped by her adult life in the United States. Her relationships with Hae Sung and Arthur function as reflective mirrors that help her recognize unresolved memories, emotional attachments, and cultural belonging. The film’s use of silence, close-ups, spatial distance, and contrasting visual tones externalizes Nora’s psychological conflict and gradual movement toward self-acceptance. This study concludes that Past Lives presents diasporic identity not merely as cultural displacement but as a humanistic process of negotiating memory, emotion, and psychological congruence.